Studies of Shapes: Subjectivity in Palaeography and Understanding - Allen, Garrick V. (New Testament studies, 2025)
This article explores the critical possibilities that arise in New Testament studies when we view palaeography as a subjective discipline. In response to recent trends in palaeography that contrive new tools and techniques for making ‘objective’ judgements regarding the dates of manuscripts, I argue that another equally valid approach is to embrace palaeography as a practice akin to aesthetics, one that relies on observation and judgements about shapes to create new contexts for interpretation. Even if palaeography is no longer considered as ‘scientific’ as it was in the late nineteenth and early twentieth centuries, there are multiple new opportunities that arise when we place palaeographic discourse and its critical practices into conversation with other disciplines.